Comparative Study of Laparoscopic vs Open Surgery for Duodenal Ulcer Perforation - fazal, Usama; shah, Abdullah; Alam, Zeeshan; Saddiqe, Hazrat Abu Bakar; Khan, Abdul Basit; Masood, Javairia Riaz (Biological and Clinical Sciences Research Journal, 2025)
Perforated duodenal ulcers are a typical surgical emergency. While open surgery has long been the standard treatment, laparoscopic techniques are gaining popularity due to their minimally invasive nature and potential for improved postoperative outcomes. Objective: To compare the outcomes of laparoscopic versus open surgery in the management of perforated duodenal ulcers. Methods: This comparative observational study included 64 patients diagnosed with perforated duodenal ulcers. Patients were assigned into two groups: Group A (n = 32) underwent laparoscopic surgery, and Group B (n = 32) underwent open surgery. Postoperative outcomes were evaluated, including operative time, duration of hospital stay, time to resume normal activities, and postoperative complications. Statistical analysis was performed using standard methods, with significance set at p ≤ 0.05. Results: Laparoscopic surgery was associated with a significantly longer operative time compared to open surgery (102.38 ± 22.62 minutes vs. 66.53 ± 11.49 minutes, p < 0.001). However, patients in the laparoscopic group experienced a significantly shorter hospital stay (8.47 ± 1.11 days vs. 10.03 ± 2.67 days, p = 0.005) and returned to normal activities sooner (15.09 ± 3.14 days vs. 19.44 ± 3.10 days, p < 0.001). Additionally, the laparoscopic group reported fewer postoperative complications compared to the open surgery group. Conclusion: Laparoscopic surgery, despite a longer operative time, demonstrates superior postoperative outcomes in the management of perforated duodenal ulcers, including reduced hospital stay, fewer complications, and faster recovery. It may be considered a preferable alternative to open surgery in suitable patients.